Reflections of Wilhelm Wundt’s lectures in Vytautas Civinskis’ diary: Application of introspection to comprehend emotional phenomena - Almonaitienė, Junona S.; Girininkaitė, Veronika (Psichologija, 2021)
The beginning of the 20th century is well known as a time of formation of psychology as an independent scientific discipline. One of the students interested in it was Vytautas Civinskis (1887–1910), who attended Wilhelm Wundt’s Psychology lectures during his agriculture (Landwirtschaft) studies at Leipzig University, in 1904–1906, and led a Diary at that time. This article presents analysis of fragments of Civinskis’ Diary related to psychology. Several artefacts found in it, preliminarily interpreted as the diarist’s introspection data related to emotional phenomena, are being discussed. The analysis verified the initial assumption and helped to understand the essence of the diarist’s research design. It was also deduced that Civinskis proceeded with the introspection at least two years after Wundt’s Psychology lectures, trying to elaborate the method. It was found that some other researchers, e. g. Flügel (1925), Viliūnas, Pacevičius and Stončius (1997) applied similar methods much later. The Civinskis’ research on his own emotional states was amateurish but performed consistently and diligently. It can be considered as one of the earliest cases of empirical research in the history of Lithuanian psychology and adds to our still incomplete knowledge of the latter.